2015
DOI: 10.1007/s11192-014-1524-z
|View full text |Cite
|
Sign up to set email alerts
|

Power laws in citation distributions: evidence from Scopus

Abstract: Modeling distributions of citations to scientific papers is crucial for understanding how science develops. However, there is a considerable empirical controversy on which statistical model fits the citation distributions best. This paper is concerned with rigorous empirical detection of power-law behaviour in the distribution of citations received by the most highly cited scientific papers. We have used a large, novel data set on citations to scientific papers published between 1998 and 2002 drawn from Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 28 publications
6
84
0
3
Order By: Relevance
“…Compared to fits of other possible candidate distributions, we find that both power-law fits are better than fits to exponential distributions, but also that other heavy-tailed distributions (among them the log-normal distribution) provide better fits. In that respect, the distribution of citations in our corpus is consistent with Brzezinski (2015), who similarly observed that other functions fit the empirical citation distributions of various disciplines better than power laws, and with Thelwall & Wilson (2015), who observed for 45 medical sub-fields that log-normal distributions are better fits to citation counts than power laws. Thelwall & Wilson (2015) further showed that for these disciplines a hooked power law is an even better fit than the log-normal distribution.…”
Section: Citation Frequency Distributionsupporting
confidence: 90%
See 3 more Smart Citations
“…Compared to fits of other possible candidate distributions, we find that both power-law fits are better than fits to exponential distributions, but also that other heavy-tailed distributions (among them the log-normal distribution) provide better fits. In that respect, the distribution of citations in our corpus is consistent with Brzezinski (2015), who similarly observed that other functions fit the empirical citation distributions of various disciplines better than power laws, and with Thelwall & Wilson (2015), who observed for 45 medical sub-fields that log-normal distributions are better fits to citation counts than power laws. Thelwall & Wilson (2015) further showed that for these disciplines a hooked power law is an even better fit than the log-normal distribution.…”
Section: Citation Frequency Distributionsupporting
confidence: 90%
“…Since the threshold x min is very high -x min = 808 means that the part of the distribution that is fitted contains only publications with at least 808 citations -, we also consider the second (local) optimum: α = 2.34 for x min = 303. The exponents α of both fits are lower than reported by both Brzezinski (2015) and Albarrán & Ruiz-Castillo (2011). This is evidence that our corpus, which is collected from a web system, is indeed different to corpora that are collected from traditional article catalogs like Web of Science or Scopus.…”
Section: Citation Frequency Distributionmentioning
confidence: 50%
See 2 more Smart Citations
“…Similarly as for other sets of scientific publications studied in the literature [56] it is characterized by a “heavy tail” of a small number of highly cited papers and the majority of papers with very few citations. Such distributions were suggested to follow a power law distribution, N ( x ) ~ x - α , with α ~ 3 [56], especially in the region of the most highly cited papers [57,58]. The theoretical model that appears to fit well to the dataset of the PSI publications has a dual character [59], with a direct mechanism describing the papers with few citations, and an indirect mechanism (citing a paper based on citations already existing) describing the highly cited papers.…”
Section: Publicationsmentioning
confidence: 99%